2019
DOI: 10.12934/jkpmhn.2019.28.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Acculturative Stress, Depression, and Quality of Life among Indonesian Migrant Workers in South Korea

Abstract: We applied descriptive statistics, Pearson's correlation coefficients, and multiple linear regression analyses with SPSS 22 program. Results: A positive correlation was shown between acculturative stress and depression and a negative correlation was found between acculturative stress and quality of life. Significant factor associated with depression was acculturative stress. Significant factors associated with quality of life were acculturative stress and social support. Conclusion: Our study findings assist n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 21 publications
3
30
0
3
Order By: Relevance
“…This finding could be explained by the previous study on Chinese migrants in Canada that found the length of stay correlated with acculturation but not with acculturative stress (Kuo & Roysircar, 2004). Also, among Indonesian migrant workers in South Korea, their length of stay did not correlate significantly with their depression symptoms and quality of life (Farah & Choi, 2019). The acculturative stress may be affected by the intensity and depth of interaction with local people and culture during the stay period, which was mediated by language skill (Rudmin, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding could be explained by the previous study on Chinese migrants in Canada that found the length of stay correlated with acculturation but not with acculturative stress (Kuo & Roysircar, 2004). Also, among Indonesian migrant workers in South Korea, their length of stay did not correlate significantly with their depression symptoms and quality of life (Farah & Choi, 2019). The acculturative stress may be affected by the intensity and depth of interaction with local people and culture during the stay period, which was mediated by language skill (Rudmin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chinese and Vietnamese migrant groups reported worse acculturative stress than Latino migrants in the United States that shared more cultural similarities than these migrant groups (Lommel & Chen, 2016). In South Korea, Indonesian migrant workers showed higher acculturative stress than migrant workers from Thailand and Vietnam, which may be explained by noticeable differences in the culture and religious characteristics between Indonesia and South Korea (Farah & Choi, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heeseung Choi, Güney Kore Seul Ulusal Üniversitesi Hemşirelik Fakültesi'nde Ruh Sağlığı Hemşireliği alanında profesör olarak çalışmaktadır 18 . Teorisyenin ergenlerde ergenlerin duygusal sıkıntısı konusunda ebeveyn-ergen arasındaki anlaşma, göçmen işçilerde kültürel stres, depresyon ve yaşam kalitesi, Koreli ergenlerde hareketsiz kalma süresi ile uyku süresi arasındaki ilişki ve uzun süreli bakımda fiziksel kısıtlamanın önündeki engellerle ilgili personel algılarına yönelik çalışmaları vardır [19][20][21][22] . ABD'de göçmen olarak yaşayan teorisyen Heeseung Choi, göçmen ergenlerin göç süreci ve sürecin ruhsal sağlıkları üzerindeki etkisi sonucu karşılaştıkları koşulları fark etmiştir.…”
Section: Kültürel Marjinallik Teorisinin Gelişimiunclassified
“…Kültürel Marjinallik Teorisi için bir diğer araştırma alanı da ölçek geliştirmedir. Araştırmacılar, kültürleşme ve kültürel stres düzeylerini ölçmek ve bu kavramlar ile ruh sağlığı sonuçları arasındaki ilişkileri açıklamak için ölçekler geliştirmişlerdir 15,41 . Buna ek olarak, kültürel yeterlilik incelenmiştir ve Choi kültürel farkındalık ölçeğinin Kore versiyonunu iyi güvenilirlikle ve yapı geçerliliği ile geliştirmek için bir araştırma ekibi ile işbirliği yapmıştır.…”
Section: Kültürel Marjinallik Teorisinin Hemşirelik Araştırmaları Ve Eğitiminde Kullanımıunclassified